Dispute settlement reports 2019. World Trade Organization. (Cambridge University Press, 2021)
These are the WTO's authorized and paginated reports in English. They are an essential addition to the library of all practising trade lawyers and a useful tool for students and academics worldwide working in the field of international economic or trade law. DSR 2019: Volume IX contains the panel and Appellate Body reports on 'United States - Countervailing Duty Measures on Certain Products from China (WT/DS437), Recourse to Article 21.5 of the DSU by China'.